Da possibilidade da aplicação do princípio da insignificância nas decisões dos tribunais de contas do Brasil - Maieto, Rosano Pierre (2019)
The present work aims to analyze the possibility that the Brazilian Audit Courts can apply, in the exercise of external control of the Public Administration, the principle of insignificance, either in the issuance of the previous opinion on the accounts annually provided by the Chief Executive, as well as in the judgment of the other management accounts, in accordance with Article 71, I and II of the Federal Constitution of 1988. The study starts from exposing the principle of insignificance and its application in criminal law, increasing trend in the jurisprudence of Superior Courts in Brazil, as a result of the theory of minimum criminal law, which delegates to other areas of the right the resolution of illicit low-intentional acts. If criminal law can disregard criminal offences of low or no social relevance, the same reasoning can be applied to the other branches of law, as in the tax, electoral or even administrative sphere. In relation to the latter, the principle of insignificance fits into the modern interpretation of the concept of legality, which no longer means strict obedience to the law, but admits its compatibility with criteria of proportionality and reasonableness, providing a more balanced and efficient action of the Public Administration. In this context, the administrative control systems take care of really significant facts and acts, highlighting the calls “bagatelas”, typical concern of the formalist bureaucracy still present in the Brazilian Public Administration. Regarding the Courts of Auditors, admitting the application of the principle of insignificance meets the principles of reasonableness, proportionality, economics and efficiency, since the excessive complexity and volume of government accounts require the activity of control to pay greater attention to the factors of higher risk and that represent a greater impact on society, by reversing the practice of the Court of Auditors in pursuing the penny to the detriment of the million. The methodology applied to this study started from the empirical analysis of the jurisprudence of the 33 (thirty-three) Courts of Accounts of Brazil, selecting those whose search criteria by the term “principle of insignificance” appears as a parameter of rationale for the solution of decisions, whether monocratic or collegiate. Among the Courts applying the principle of insignificance was highlighted to the Court of Auditors of the Union, by the fact of exercising control over the accounts of the federal government, as well as in relation to the Court of Auditors of the States of Minas Gerais, because that Court is responsible for the judgment of the accounts of 853 (eight hundred and fifty three) municipalities, the largest quantity among the Brazilian States, beyond the accounts of the state government itself. It is also the Court in which the application of the insignificance principle is best consolidated. The experiments studied here aim to investigate the possibility that the adoption of the principle of insignificance by the Courts of Accounts of Brazil will become the rule and that, thus, it can contribute to a better efficiency and effectiveness of external control in the supervision of the application of public resources.